Early Postnatal Heart Rate Variability in Healthy Newborn Infants - Oliveira, Vânia; von Rosenberg, Wilhelm; Montaldo, Paolo; Adjei, Tricia; Mendoza, Josephine; Shivamurthappa, Vijayakumar; Mandic, Danilo; Thayyil, Sudhin (Frontiers in Physiology, 2019)
Background Despite the increasing interest in fetal and neonatal heart rate variability analysis and its potential use as a tool for early disease stratification, no studies have previously described the normal trends of heart rate variability in healthy babies during the first hours of postnatal life. Methods We prospectively recruited 150 healthy babies from the postnatal ward and continuously recorded their electrocardiogram (ECG) during the first 24 hours of postnatal life. Five-minute segments of the ECG (non-overlapping time-windows) with more than 90% consecutive good quality beats were included in the calculation of hourly medians and interquartile ranges to describe heart rate variability (HRV) trends over the first 24h of life. We used multilevel mixed effects regression with auto-regressive covariance structure for all repeated measures analysis, and T-tests to compare group differences. Non-normally distributed variables were log-transformed. Results Nine out of 16 HRV metrics (including heart rate) changed significantly over the 24 hours (Heart rate p<0.01; Standard deviation of the NN intervals p=0.01; Standard deviation of the Poincaré plot lengthwise p <0.01; Cardiac sympathetic index p<0.01; Normalized high frequency power p=0.03; Normalized low frequency power p <0.01;Total power p<0.01; HRV index p=0.01; Parseval index p=0.03), adjusted for relevant clinical variables. We observed an increase in several HRV metrics during the first 6h followed by a gradual normalization by approximately 12h of age. Between 6 and 12 hours of age, only heart rate and the normalized low frequency power changed significantly, while between 12 and 18 hours no metric, other than heart rate, changed significantly. Analysis with multilevel mixed effects regression analysis (multivariable) revealed that gestational age, reduced fetal movements, cardiotocography and maternal chronic or pregnancy induced illness were significant predictors of several HRV metrics. Conclusion Heart rate variability changes significantly during the first day of life, particularly during the first 6h. The significant correlations between HRV and clinical risk variables support the hypothesis that HRV is a good indicator of overall well-being of a baby and is sensitive to detect birth-related stress and monitor its resolution over time.